WAFA METHOD IN LEARNING TAHSIN TO READ AL-QURAN IN BINA INSAN PALU INTEGRATED ISLAMIC ELEMENTARY SCHOOL - Hidayat, Ian; Sidik, Sidik; Kamaruddin, Kamaruddin; Djamil M Nur, Muhammad (Department of Islamic Education, Postgraduate Program Univercity for Islamic Studies Palu, 2023)
This article discusses the use of wafa method in learning tahsin to read al-quran in a elementary school in Palu city, Central Sulawesi. The research used a qualitative method with data collection techniques such as direct observation, in-depth interviews, and document analysis. The research findings show that planning for learning the Qur'an using the Wafa method includes the syllabus and learning implementation plan, learning objectives, learning materials, learning media, and evaluation. Applying the Wafa method to learning tahsin in the Qur'an uses quantum teaching: grow, experience, name, demonstrate, repeat, and celebrate. However, some methods include opening, experience, teaching, assessment, and closing. The results of tahsin learning in reading the Qur'an for students using the Wafa method at the Bina Insan Integrated Islamic Elementary School in Palu are that it is easier for students to recognize the letters, students can read the Qur'an well and correctly, students are also able to read the Qur'an using the hijaz tone with the correct pattern, simplified, and students are also able to write the Qur'an with Ustmani khat.